An Anthropological Study of Hospitality : The Innkeeper and the Guest - Touval, Amitai (Springer International Publishing : Imprint: Palgrave Macmillan, 2017)
This volume explores recent developments in the practice of hospitality, as well as the curious, precarious relationship between guests and their hosts. Drawing from personal interactions with an aging innkeeper called Herr Klaus and modern Airbnb hostess Gretchen, Amitai Touval offers a touching and illuminating account of how the rise of Airbnb has forged new standards of generosity, hostility, and accountability. An Anthropological Study of Hospitality is a must-read for anyone who has wondered about the intricate social cues involved in such a seemingly simple exchange. Amitai Touval is Adjunct Assistant Professor at the Zicklin School of Business at Baruch College, City University of New York, USA. He is also Social Media Director of ITAP International.
Keywords: Social sciences.; Ethnology.; Idealism, German.; Ethnography.; elektronické knihy; electronic books